Edukasi Anti-Bullying Berbasis Sekolah Inklusif pada Pendidikan Dasar - Novita Budiarti; Siti Umi Latifah; Budi Santoso (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Bullying in primary education becomes increasingly complex in inclusive school settings because students with special educational needs, learning difficulties, and characteristics perceived as different face a greater risk of victimization and social exclusion. This study aims to analyze anti-bullying education strategies aligned with the principles of inclusive education and to formulate a conceptual framework integrating the roles of teachers, students, parents, peers, school policies, and school culture. This study employed a qualitative library research design. The data were drawn from 24 scholarly articles, including nationally accredited journal articles, international articles indexed in Scopus, and systematic reviews and meta-analyses. The data were analyzed using qualitative content analysis through coding, categorization, comparison of findings, and thematic development. The findings indicate that inclusive school-based anti-bullying education should be developed through five key components: identifying student vulnerabilities, understanding the impacts of bullying, implementing accessible and participatory educational strategies, strengthening collaboration among teachers, parents, and peers, and adopting a whole-school approach. The proposed framework is preventive, participatory, collaborative, restorative, sustainable, and responsive to the diverse needs of learners. This study underscores the importance of positioning inclusivity as a fundamental principle in designing anti-bullying policies, learning activities, reporting mechanisms, student support, case management, and program evaluation in primary education.